Islamic and Western ethics in communication - Mokhtar, Aida (2019)
There appears to be a demarcation between Islamic and Western ethics. Ethics are important in Islam in terms of ensuring that communication and other practices in life adhere to Islam. There are instances when Western and Islamic ethics meet but the sources of these forms of ethics is what differentiates them. Islamic ethics is mainly sourced by the Qur'an and Sunnah whereas Western ethics have a multitude of sources and may differ in their substance.